Quick water‐selective excitation of fast relaxing tissues with 3D UTE sequences. Issue 2 (25th February 2013) - Springer, Fabian; Steidle, Günter; Martirosian, Petros; Grosse, Ulrich; Syha, Roland; Schabel, Christoph; Claussen, Claus D.; Schick, Fritz
<x xml:space="preserve">Abstract</x> Purpose The aim of this study was to implement a time effective 1‐1 double pulse water‐selective excitation (WE) into a three‐dimensional ultrashort echo time (UTE) sequence (WE‐UTE) for visualization of short‐T2 tissues with positive contrast and sufficient suppression of surrounding fat. Methods First, an analytical description of magnetization components in the steady state applying WE‐UTE was derived and results were compared with numerical simulations based on Bloch's equations. Parameters were optimized for best positive contrast between short‐T2 tissues and fat under consideration of variable relaxation properties over a broad range. Maximal signal yield and signal efficiency of on‐resonant protons were compared with UTE sequences with and without off‐resonance fat saturation (FatSat). WE‐UTE was exemplarily applied for in‐vivo musculoskeletal imaging on a 3T whole‐body MR unit. Results Steady state magnetization of WE‐UTE could be described analytically and showed excellent accordance with numerical simulations. Even for tissues with T2 = 1 ms WE‐UTE resulted in 79% of maximal signal yield of UTE without FatSat and was more efficient regarding signal yield if compared with UTE with FatSat. Using WE‐UTE in‐vivo tendons and ligaments could be well delineated with positive contrast to surrounding fat. Conclusion WE‐UTE provides a quick method for visualizing short‐T2 tissues with positive contrast. Magn Reson Med 71:534–543, 2014. © 2013 Wiley Periodicals, Inc.